A model of a repoint track switch for control - Nick Wright; Sam Bemment; Christopher Ward; Roger Dixon (2014)
Track switching provides necessary flexibility to a rail network, allowing vehicles to change routes when necessary. Track switches, however, have historically been prone to failure. To increase asset reliability, a concept for a novel design of switch has been developed which allows multi-channel actuation through a novel actuation and locking mechanism, under a project titled 'Repoint'. This paper describes a mathematical model of the operation a novel Repoint track switch. The model was derived from a first principles physical analysis of the Repoint concept design. The structure of the model mimics the physical structure of the design. Each physical component has an individual sub-model. The model has been used to estimate the actuator drive requirements for a case study mainline switch installation. It has been found that a Repoint track switch could be run from an existing UK signalling power supply. It is anticipated that this model will be used as the basis for a control system design activity for a technology demonstrator installation currently under construction.